Simulation Study of 2.4 GHz Rectangular Microstrip Patch Antenna for Sensing Sugar Content Detection - Queen Hesti Ramadhamy -; Annisa Maulidya; Baik Budi; Refki Budiman (Electrical Engineering Department Faculty of Engineering Universitas Andalas, 2025)
This study presents a simulation-based analysis of 2.4 GHz rectangular microstrip patch antenna for sensing sugar content in aqueous solutions. The antenna was designed and simulated using software with performance evaluated based on return loss and resonance frequency shifts in response to changes in the dielectric properties of the sugar solution. The primary objective was to assess the sensitivity of the rectangular microstrip antenna to variations in sugar concentration. The result show that the antenna exhibits measurable resonance frequency shifts as the sugar content in the solution increases, indicating the potential of microstrip antennas as effective, non-invasive sensors for liquid concentration monitoring. These findings contribute to the development of microwave-based sensing technologies, offering insights into the application of microstrip patch antennas for sugar detection and other similar application.